SUSTAINABLE PACKAGING SOLUTIONS AND INNOVATION - Zaenal Aripin; Arif Budi Raharja; Nyoman Dwika Ayu Amrita (PT. Kreatif Indonesia Satu, 2025)
Background: The global packaging industry faces mounting pressure from environmental degradation, stricter regulatory frameworks, and rising stakeholder expectations regarding sustainability. Conventional packaging practices, heavily reliant on single-use plastics and non-recyclable materials, contribute significantly to pollution, resource depletion, and carbon emissions. The COVID-19 pandemic further exposed vulnerabilities in packaging supply chains while simultaneously accelerating consumer awareness of environmental responsibility. As a result, organizations must urgently innovate toward sustainable packaging solutions that balance ecological performance with economic viability and operational efficiency. Aims: This study investigates the drivers, implementation approaches, barriers, and performance outcomes of sustainable packaging innovation across manufacturing and retail organizations in Southeast Asia, with a focus on developing an evidence-based framework for practitioners and policymakers. Method: A mixed-methods design was employed, combining a quantitative survey of 312 senior managers across Southeast Asia (response rate 26%) using 87 validated Likert-scale items, and qualitative case studies from 28 cross-sector organizations through 94 semi-structured interviews averaging 75 minutes each, supplemented by direct observation and document analysis. Quantitative data were analyzed using multivariate regression and correlation techniques (e.g., r = 0.67 for the communication variable); qualitative data underwent systematic thematic coding with triangulation. Results: Findings reveal that 78% of organizations initiated sustainable packaging transformation within the last three years, driven primarily by regulatory compliance (72%) and market demands for eco-friendly products (68%). Phased implementation approaches supported by change management practices — with a budget allocation of 15–20% — achieved success rates of 71–83%. Organizations adopting sustainable packaging reported an average 34% reduction in material waste (range 18–67%), a 28% improvement in customer satisfaction, a 22% increase in brand equity scores, and an 18% reduction in long-term packaging costs. Organizational resistance (68%) emerged as the primary barrier, effectively mitigated through early stakeholder involvement (+140%) and comprehensive employee training programs (+165%). Contribution: This study develops an evidence-based framework for advancing sustainable packaging capabilities, offering actionable insights for industry practitioners, organizational leaders, and environmental policymakers navigating the circular economy transition in Southeast Asia.